THE EFFECT OF MOZART MUSIC IN REDUCING ANXIETY OF ENGLISH SPEAKING IN PUBLIC - Dzur Rif'ah Mahmudah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2013)
The study used an experimental method namely a quasi-experimental design. The population of the study was consist of 260 subjects from ten classes. The sample one was purposive sampling. The researcher collected data by using four instruments, they are the questionnaire, observation, and scale of behavior. The result showed that Mozart gave effect in reducing subjects’ anxiety of English speaking in public. It was proved by the total subjects is 8 students for very high anxiety and 7 students for very low anxiety before given treatments; while after given treatment, there are only 4 subjects for very high anxiety and 10 subjects for very low anxiety (look at table 7 and 9). In other hands, the data support by Paired Sample Correlation table showed that score between pretest and posttest by 32 respondents = 0,874; the significance or p was 0,000. The norm said that if the significance showed under 0, 05 (p 0, 05), it means that H1 is accepted and H0 is refused. So, the conclusion for the research is Mozart Effect can reduce the students’ anxiety of English speaking in public. The findings of the research were significant because of p 0, 05.Keywords: Effect, Mozart, Music, Anxiety, Speaking